Stroke literacy among people attending Klinik Rawatan Keluarga (KRK) in Hospital Universiti Sains Malaysia (HUSM) - Manab, Ainul Wahidah Abd (Universiti Sains Malaysia, 2012)
Stroke is the third most common cause of mortality in the developed world and is also the leading cause of adult neurological disability. Due to ageing populations worldwide, it has been estimated that by 2020 stroke will be the leading cause of lost healthy life-years. To combat the effects of stroke, the knowledge regarding sign and symptom and risk factor of stroke among people are very important in order to prevent from getting the stroke. The aim of the study was to assess and evaluate the level of knowledge of stoke sign and symptom and risk factor among people attending Klinik Rawatan Keluarga (KRK), Hospital Universiti Sains Malaysia, (HUSM). The study was conducted between September 2011 to June 2012. Data was collected using self administered questionnaire. A total score of 10 and above indicate good knowledge regarding stroke. Descriptive studies were used to describe the characteristic of respondents. Chi square test were used to test the association between sociodemographic data and total score knowledge of stroke. The good total score knowledge of stroke in this study is 63%. The only sociodemographic data which having not association toward total score knowledge of stroke is gender and the ethnic, meanwhile others risk factor identified by respondents was hypertension, recurrent smoking and also the heart disease. While the sign and symptoms that highly know from the respondents were 'sudden numbness or weakness of the arm or leg, especially on one side of body' and 'sudden dizziness'. Therefore, the data obtained in this study may be serving guideline for early detection and prevention of the stroke in our community.